Laser frenectomy – a technical note / Ikhwan Hakimi Mohamad, Siti Lailatul Akmar Zainuddin and Irfan Mohamad - Mohamad, Ikhwan Hakimi; Zainuddin, Siti Lailatul Akmar; Mohamad, Irfan (Faculty of Medicine, 2022)
Labial frenulum is a band of tissues that connects the lip to the gum inside the oral cavity. In a highly-attached upper labial frenulum, a procedure known as frenectomy is usually performed under local anaesthesia. The indications for removal may include frequently traumatized soft tissues, gum recession, difficulties in maintaining good oral hygiene as well as for orthodontic purposes. There are various techniques in performing frenectomy including conventional scalpel and laser. Nowadays, laser is becoming the first choice for use in frenectomy as it is more time-saving, less painful and shows low-to-none intra- and post-operative complication. In this paper, we report a case of laser frenectomy procedure at the upper labial area, its complication and how we tackled it.